2019
DOI: 10.1016/j.pneurobio.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage biology in the peripheral nervous system after injury

Abstract: Neuroinflammation has positive and negative effects. This review focuses on the roles of macrophage in the PNS. Transection of PNS axons leads to degeneration and clearance of the distal nerve and to changes in the region of the axotomized cell bodies. In both locations, resident and infiltrating macrophages are found. Macrophages enter these areas in response to expression of the chemokine CCL2 acting on the macrophage receptor CCR2. In the distal nerve, macrophages and other phagocytes are involved in cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
250
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(257 citation statements)
references
References 295 publications
(394 reference statements)
4
250
0
3
Order By: Relevance
“…This finding suggests that Iba1+ cells are in a physical position to directly influence nociceptive neurons after injury and may potentially contribute to the development of neuropathic pain. Indeed, macrophage‐neuron interactions have been suggested to be crucial for peripheral sensitization and neuropathic pain (Marchand, Perretti, & McMahon, ; Moalem & Tracey, ; Santa‐Cecília et al, ; Vega‐Avelaira et al, ; Zigmond & Echevarria, ). The timing of this migration is also suggestive: Mice have been shown to develop mechanical allodynia during the first 2–3 days after nerve injury (Richner et al, ; Richner, Bjerrum, Nykjaer, & Vaegter, ), which coincides with the formation of the “ring‐like” structures we report here.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that Iba1+ cells are in a physical position to directly influence nociceptive neurons after injury and may potentially contribute to the development of neuropathic pain. Indeed, macrophage‐neuron interactions have been suggested to be crucial for peripheral sensitization and neuropathic pain (Marchand, Perretti, & McMahon, ; Moalem & Tracey, ; Santa‐Cecília et al, ; Vega‐Avelaira et al, ; Zigmond & Echevarria, ). The timing of this migration is also suggestive: Mice have been shown to develop mechanical allodynia during the first 2–3 days after nerve injury (Richner et al, ; Richner, Bjerrum, Nykjaer, & Vaegter, ), which coincides with the formation of the “ring‐like” structures we report here.…”
Section: Discussionmentioning
confidence: 99%
“…These innate immune cells provide critical phagocytic functions . But additionally, these innate immune cells provide other functions essential to nerve regeneration, including re‐myelination and functional recovery, which are not yet entirely understood, After this Wallerian degeneration process is complete, SCs progressively assume long processes and align on the basal lamina of the intact distal nerve environment (bands of Bungner), providing a permissive growth environment for the regenerating axons that emerge from the proximal nerve stump . As axon growth proceeds from proximal to distal nerve, remyelination of the axons is initiated primarily by axon‐derived neuregulin‐1 signaling through SCs’ ErbB receptors .…”
Section: Biology Of Nerve Regeneration Across a Defectmentioning
confidence: 99%
“…The repair of nerve defects using a pseudosynovial sheath demonstrated that plasma exudates from the proximal and distal nerve stumps fill the empty tube volume, and provide a deposition of extracellular matrix (ECM), including a fibrin matrix, that allows for innate immune system cell migration . While the earliest (<4 days) macrophages are derived from tissue resident macrophages, subsequent macrophages are primarily hematogenous‐derived . Due to the hypoxic nature of this environment, macrophages support a substantial amount of angiogenesis enabling endothelial cell recruitment and vessel formation (Figure 1A).…”
Section: Biology Of Nerve Regeneration Across a Defectmentioning
confidence: 99%
“…The immune microenvironment of injured nerves plays a critical role in the regulation of nerve regeneration after injury 5,6 . Debris resulting from degenerated axons and myelin can inhibit axonal regrowth and should be cleared to create a favorable microenvironment for subsequent nerve regeneration 7 . These debris are mainly removed by macrophages, 7,8 which can be increased by activating the toll‐like receptor 4 (TLR4) signaling pathway of the innate immune system via lipopolysaccharide (LPS) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Debris resulting from degenerated axons and myelin can inhibit axonal regrowth and should be cleared to create a favorable microenvironment for subsequent nerve regeneration 7 . These debris are mainly removed by macrophages, 7,8 which can be increased by activating the toll‐like receptor 4 (TLR4) signaling pathway of the innate immune system via lipopolysaccharide (LPS) 9 . It has been reported that LPS can accelerate myelin debris clearance during Wallerian degeneration, and promote subsequent axon regeneration via enhanced macrophage recruitment in neurotmesis 8,10 .…”
Section: Introductionmentioning
confidence: 99%